2007
DOI: 10.2337/db06-1432
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of Adiponectin Receptors 1 and 2 on Energy Metabolism

Abstract: The adipocyte-derived hormone adiponectin regulates glucose and lipid metabolism and influences the risk for developing obesity, type 2 diabetes, and cardiovascular disease. Adiponectin binds to two different seven-transmembrane domain receptors termed AdipoR1 and AdipoR2. To study the physiological importance of these receptors, AdipoR1 gene knockout mice (AdipoR1 Ϫ/Ϫ ) and AdipoR2 gene knockout mice (AdipoR2 Ϫ/Ϫ ) were generated. AdipoR1 Ϫ/Ϫ mice showed increased adiposity associated with decreased glucose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
209
1
12

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(240 citation statements)
references
References 52 publications
(69 reference statements)
18
209
1
12
Order By: Relevance
“…Additionally, it was found that IPo improved mitochondrial function, reduced oxidative stress, and increased nitric oxide levels in an adiponectin-dependent manner. Mechanistically, the beneficial effects of adiponectin in IPo appeared to be specifically mediated by the activation of adiponectin receptor 1 (AdipoR1) but not by AdipoR2, thereby confirming previous results demonstrating that AdipoR1 and AdipoR2 may regulate different mechanisms (7). Of note, IPo also increased the interaction between AdipoR1 and caveolin-3 (Cav3), a protein that appears to be critical for AdipoR1 function.…”
supporting
confidence: 85%
“…Additionally, it was found that IPo improved mitochondrial function, reduced oxidative stress, and increased nitric oxide levels in an adiponectin-dependent manner. Mechanistically, the beneficial effects of adiponectin in IPo appeared to be specifically mediated by the activation of adiponectin receptor 1 (AdipoR1) but not by AdipoR2, thereby confirming previous results demonstrating that AdipoR1 and AdipoR2 may regulate different mechanisms (7). Of note, IPo also increased the interaction between AdipoR1 and caveolin-3 (Cav3), a protein that appears to be critical for AdipoR1 function.…”
supporting
confidence: 85%
“…The most simple interpretation of this observation is that there would be a corresponding reduction in the availability of these receptors to bind adiponectin and a subsequent decline in gAdand fAd-stimulated effects. Many, but not all, studies in animal models [44] and humans [13,14] have also suggested an important role for alterations in ADIPORs in the pathogenesis of insulin resistance and diabetes. Of particular interest, Adipor1 −/− mice showed increased Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Representative western blots are shown, with quantitative data expressed as means±SEM of at least three independent experiments. *p<0.05 with respect to control adiposity associated with decreased glucose tolerance and energy expenditure, whereas Adipor2 −/− mice were lean and resistant to high-fat diet-induced obesity [44]. In human studies, Steinberg's group has shown that skeletal muscle from obese or obese type 2 diabetic patients showed decreased sensitivity to gAd, yet ADIPOR1 levels were higher, suggesting that aspects downstream of the receptor may inhibit adiponectin action [13].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of adipoR1 has previously been reported to increase during conditions of increased fat oxidation and insulin sensitivity, including weight loss (39) and aerobic exercise training (40), and we speculate that the downregulation of adipoR1 may be a mechanism by which high-fat diet induces insulin resistance. A recent study examining the effects of knockout of adipoR supports this because knockout of adipoR1 increased adiposity and insulin resistance, whereas knockout of adipoR2 increased insulin sensitivity and prevented high-fat diet-induced obesity (41). In rodents, both AdipoR1 and adipoR2 expression are reduced in response to refeeding (42).…”
Section: Figmentioning
confidence: 94%